MODEL EKONOMI PERBERASAN: ANALISIS INTEGRASI PASAR DAN SIMULASI KEBIJAKAN HARGA - FANNY WIDADIE; ADI SUTANTO (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2012)
Rices are strategic and important food for Indonesian. The aims of this research are to make rice economic model that to know (1) the condition of rice market integration; (2) Several factors that affecting production, demand, import and price rice; and (3) the affecting government policies to price of rice. Data analysis is using cointegration-test with Error Correction Model approach, Two Stages Least Square (2SLS) method and policy simulation. Research result shows that there is market integration between domestic rice prices with world rice prices.